Integration of Scientific Information through Linked Data : Preliminary Report - Michelan, Gastón (2016)
By implementing Linked Open Data principles throughout the scientific community, it is possible to make publications more visible and foster collaboration, both between universities, researching groups and partners. However, data should be curated and published, and a mature infrastructure needs to be provided to support it. In this work, we analyse the Linked Data’s weaknesses and propose an application prototype to evaluate the state-of-the-art methodologies and tools. As case of study, data from the authors’ researching groups will be publicly available in an attempt to integrate the scientific data of the Argentinian community which is an open issue. We plan to use this data to generate bottom-up methodological guidelines and thus enrich ontology-based conceptual models.